Immunohistochemical expression of macrophages in chronic periapical lesions (Research, Society and Development, 2021)
Objective: To analyze the expression of macrophages in periapical granulomas (PGs) and radicular cysts (RCs). Methodology: We selected 264 cases of chronic periapical lesions stored at the Laboratory of Pathology, Dental School of Pernambuco (FOP)/UPE, including 89 PGs and 175 RCs. Seventy-nine cases, 23 PGs and 56 RCs, were submitted to immunohistochemical analysis by the streptavidin-biotin method using anti-CD68 antibody. The chi-square and Fisher’s exact tests were used to determine the existence of associations with categorical and clinical variables, adopting a 95% confidence level (p≤0.05). Results: We observed immunoexpression of CD68 in 83% of cases. The number of CD68+ cells (score 3 or 4) was higher in PGs, with predominantly intense staining. Significant differences in the number of CD68+ cells and staining intensity were observed between the chronic periapical lesions analyzed. Conclusion: The presence of CD68+ cells in periapical tissues may indicate the development, maintenance and/or severity of the inflammation-mediated immune response, which is more intense in PG.